Synthesis of hydrophobically modified berberine derivatives with high anticancer activity through modulation of the MAPK pathway. (7th August 2020) - Wang, Lizhen; Yang, Xueliang; Li, Xiaobin; Stoika, Rostyslav; Wang, Xue; Lin, Houwen; Ma, Yukui; Wang, Rongchun; Liu, Kechun
Abstract : Linoleic acid-modified berberine derivative induces apoptosis of A549 cells and affects the expression of proteins associated with the MAPK pathway. Abstract : Berberine is a naturally occurring isoquinoline alkaloid that has great potential as a lead compound for the development of highly effective anti-cancer agents. In this study, some hydrophobically modified berberine derivatives were synthesized and characterized by NMR spectroscopy and high resolution mass spectrometry. All the synthesized compounds were subjected to cytotoxicity screening against various cancer cell lines, and the results indicated that most of the berberine derivatives exhibited high cytotoxicity with IC50 values ranging from 3.24 to 7.30 μM. The linoleic acid-modified berberine derivative 8 was chosen for further studies, and was shown to significantly inhibit proliferation and induce apoptosis of A549 adenocarcinoma cells. Western Blot analysis revealed that compound 8 affected the expression of proteins associated with cell proliferation and apoptosis, particularly proteins associated with the MAPK pathway, such as p-ERK, p-38 and p-JNK. Compound 8 also strongly inhibited migration of A549 cells in a wound closure assay. All of these results indicate that berberine derivative 8 is a promising anti-cancer drug candidate for further biological investigation.